Highly dispersed tantalum-scandium composite oxide, preparation method and application thereof in catalytic preparation of 1,3-butadiene

CN122974355APending Publication Date: 2026-10-27BEIJING INST OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611392737.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-09
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0006]本发明旨在解决现有技术中Ta基催化剂活性组分易团聚形成强酸中心、导致乙烯及积碳等副反应严重、活性组分利用率低的技术问题,提供一种活性组分高分散孤立分布、酸中心强度可控、在总负载量低于1 wt%的条件下即具有优异催化性能的钽钪复合氧化物及其制备方法,以及其作为催化剂在制备1,3-丁二烯中的应用

Benefits of technology

(1)本发明提供一种高分散钽钪复合氧化物催化剂,包含有序介孔二氧化硅载体,以及限域于所述载体介孔孔道内表面的活性组分;所述活性组分由钽的氧化物和钪的氧化物共同组成,二者以非晶态、亚纳米级团簇或孤立原子形式高度分散。本发明所提供的高分散钽钪复合氧化物,引入钪氧化物作为结构助剂,在原子尺度上对TaOx物种进行化学隔离,进一步提高了孤立活性位点的分散稳定性和抗烧结能力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a kind of high-dispersion tantalum-scandium composite oxides and preparation method and application in catalytic preparation 1,3-butadiene.The composite oxide is mesoporous silica as carrier, and active component is composed of tantalum and scandium oxide, total loading is not more than 1.0 wt%, and active component is highly dispersed in carrier mesoporous channel inner surface in amorphous state, sub-nanometer cluster or isolated atom form.The composite oxide is prepared by double solvent-limited space in-situ growth method.Using the composite oxide to catalyze ethanol-acetaldehyde mixture to prepare butadiene reaction, under the condition that total loading is only 0.62 wt%, butadiene selectivity is as high as 82.1%, and ethylene selectivity is as low as 0.9%, so that strong acid center and side reaction caused by active component clustering are eliminated from the source, and the catalyst stability is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of heterogeneous catalysis technology, specifically relating to a highly dispersed tantalum-scandium composite oxide, its preparation method, and its application in the catalytic preparation of 1,3-butadiene. Background Technology

[0002] 1,3-Butadiene is an important monomer for the synthesis of rubber and engineering plastics. The route for preparing butadiene from ethanol via acetaldehyde intermediates has attracted considerable attention due to its green and renewable properties. The key steps in this route lie in the aldol condensation of acetaldehyde and the subsequent C-C coupling reaction, which requires Lewis acid center catalysis.

[0003] Existing technologies generally employ impregnation to load Lewis acid components such as Ta, Nb, and Zr onto the surface of supports such as SiO2. However, the traditional impregnation method has the following prominent drawbacks: (1) Active components are prone to agglomeration: During drying and calcination, metal precursors tend to migrate and aggregate on the support surface, forming nano- or even submicron-sized clusters or microcrystals. These clusters have strong Lewis acid centers with unsaturated coordination on their surfaces; (2) Strong acid centers trigger side reactions: The strong acid sites generated by agglomeration can catalyze the intramolecular dehydration of ethanol to generate ethylene and promote the excessive polymerization of reaction intermediates, leading to carbon deposition and rapid catalyst deactivation; (3) Low atom utilization efficiency: To compensate for the effective surface area lost due to agglomeration of active sites, traditional catalysts often require a high loading of active components, resulting in a waste of precious metal resources and increased costs.

[0004] Chinese patent application CN 114160144 A discloses a Ta / SiO2 catalyst for the production of butadiene from ethanol, prepared by an equal-volume impregnation method. Although this method can achieve a certain butadiene yield, the catalyst stability is insufficient due to severe agglomeration of the active component, high selectivity for ethylene and heavy byproducts.

[0005] Therefore, developing a catalyst that can fundamentally inhibit the aggregation of active components, achieve near-atomic dispersion, and exhibit excellent catalytic performance at extremely low loading, as well as its controllable preparation method, has significant industrial application value and scientific significance. Summary of the Invention

[0006] This invention aims to solve the technical problems in the prior art where the active component of Ta-based catalysts easily agglomerates to form strong acid centers, leading to serious side reactions such as ethylene and carbon deposition, and low utilization rate of active components. It provides a tantalum-scandium composite oxide with highly dispersed and isolated distribution of active components, controllable acid center strength, and excellent catalytic performance even with a total loading of less than 1 wt%, as well as its preparation method and its application as a catalyst in the preparation of 1,3-butadiene.

[0007] Specifically, the present invention provides the following technical solution: A first aspect of the present invention provides a highly dispersed tantalum-scandium composite oxide comprising a mesoporous silica support and an active component located on the inner surface of the mesoporous channels of the support; The active component is composed of tantalum oxide and scandium oxide, which are highly dispersed in the form of amorphous, sub-nanometer clusters or isolated atoms. Based on the total mass of the highly dispersed tantalum-scandium composite oxide, the total loading of tantalum and scandium elements in the active component does not exceed 1.0 wt%, and the molar ratio of scandium to tantalum is 0.2-0.8.

[0008] According to an embodiment of the present invention, the loading of tantalum is 0.3-0.8 wt%, and the loading of scandium is 0.05-0.25 wt%.

[0009] According to an embodiment of the present invention, the mesoporous silica carrier is SBA-15, which has a specific surface area ≥600 m² / g, a pore size of 5-12 nm, and a pore volume of 0.8-1.5 cm³ / g.

[0010] A second aspect of the present invention provides a method for preparing highly dispersed tantalum-scandium composite oxide, comprising the following steps: (1) Dry the mesoporous silica support under vacuum at 120-180 °C for 8-16 hours, transfer it to an inert atmosphere, add anhydrous hydrophobic organic solvent, and stir to disperse to form a suspension; (2) While stirring, add dropwise a mixed aqueous solution containing tantalum precursor and scandium precursor to the suspension. The volume of the mixed aqueous solution is 0.9-1.1 times the pore volume of the carrier. After the addition is complete, continue stirring for 0.5-2 hours and let stand. (3) Seal the system obtained in step (2) and let it stand at 20-40 ℃ for 18-36 hours to carry out slow hydrolysis in the confined space; (4) Filter, wash, and dry under normal pressure; (5) Under air atmosphere, heat to 450-600 ℃ at a heating rate of 0.5-2 ℃ / min, calcine at constant temperature for 3-6 hours, and cool naturally to obtain the highly dispersed tantalum-scandium composite oxide.

[0011] According to an embodiment of the present invention, the anhydrous hydrophobic organic solvent in step (1) is selected from one or more of n-hexane, cyclohexane, and n-heptane; and / or The tantalum precursor in step (2) is selected from one or two of pentaethanol tantalum and pentabutoxide tantalum, and the scandium precursor is selected from one or two of scandium nitrate and scandium chloride.

[0012] According to an embodiment of the present invention, in the mixed aqueous solution in step (2), the molar ratio of tantalum to scandium is 1:(0.2-0.8), and the total loading of tantalum and scandium does not exceed 1.0 wt%.

[0013] According to an embodiment of the present invention, the aging temperature in step (3) is 25-35 ℃ and the aging time is 24 hours.

[0014] According to an embodiment of the present invention, the temperature of the atmospheric pressure drying in step (4) is 60-100 °C, and the time of the atmospheric pressure drying is 4-8 hours.

[0015] According to an embodiment of the present invention, the heating rate in step (5) is 1 ℃ / min, the calcination temperature is 500-550 ℃, and the constant temperature time is 4 hours.

[0016] A third aspect of the present invention provides a highly dispersed tantalum-scandium composite oxide, obtained according to the preparation method described in the second aspect.

[0017] A fourth aspect of the present invention provides a method for preparing 1,3-butadiene by catalytic reaction of an ethanol-acetaldehyde mixture, comprising: using a mixture of ethanol and acetaldehyde as raw material, adding the highly dispersed tantalum-scandium composite oxide described in the first aspect or the highly dispersed tantalum-scandium composite oxide described in the third aspect, and carrying out a catalytic reaction; According to an embodiment of the present invention, the molar ratio of ethanol to acetaldehyde is (2.0-2.5):1; According to an embodiment of the present invention, the reaction temperature is 300-400 °C, the reaction pressure is atmospheric pressure, and the feed mass hourly space velocity is 0.5-2.0 h⁻¹. - ¹.

[0018] According to a preferred embodiment of the present invention, the reaction temperature is 340-370 °C, and the feed mass hourly space velocity is 0.8-1.5 h⁻¹. - ¹.

[0019] The present invention has at least the following significant beneficial effects: (1) This invention provides a highly dispersed tantalum-scandium composite oxide catalyst, comprising an ordered mesoporous silica support and an active component confined within the mesoporous channels of the support; the active component is composed of tantalum oxide and scandium oxide, both highly dispersed in amorphous, sub-nanometer clusters or isolated atoms. The highly dispersed tantalum-scandium composite oxide provided by this invention introduces scandium oxide as a structural aid, thereby enhancing the atomic-scale dispersion of TaO. x Chemical isolation of species further improves the dispersion stability and anti-sintering ability of isolated active sites.

[0020] (2) The highly dispersed tantalum-scandium composite oxide provided by this invention can achieve excellent catalytic performance under extremely low conditions where the total loading of active components does not exceed 1 wt%. The butadiene selectivity can reach more than 82%, and the ethylene selectivity is less than 1%. The atom utilization efficiency of the active components is much higher than that of traditional catalysts. As a catalyst, it has excellent stability and its performance does not decline significantly after running continuously for tens of hours, showing good prospects for industrial application.

[0021] (3) Highly dispersed tantalum-scandium composite oxides were prepared by using a dual-solvent-confined space in-situ growth method, which inhibited the migration and aggregation of active components on the surface of the support from the source, realized the near-atomic dispersion of active components in the mesoporous channels, and eliminated the strong acid cluster centers that would trigger ethylene and carbon deposition side reactions. Detailed Implementation

[0022] The embodiments of the present invention are described in detail below. These embodiments are exemplary and intended to explain the present invention, and should not be construed as limiting the present invention.

[0023] This invention provides a highly dispersed tantalum-scandium composite oxide, which is prepared by a dual-solvent-confined space in-situ growth method, comprising the following steps: Step (1): Carrier pretreatment The ordered mesoporous silica support is vacuum dried to remove physically adsorbed water, then transferred to an inert atmosphere-protected environment. An anhydrous hydrophobic organic solvent is added and stirred to disperse the solution into a suspension. Vacuum drying allows for precise control of the density and state of silanol groups on the support surface, providing controllable nucleation sites for the uniform anchoring of active components within the pores. The inert atmosphere prevents moisture from prematurely entering the pores and interfering with the subsequent confined introduction process.

[0024] According to a specific embodiment, the mesoporous silica carrier is SBA-15, with a specific surface area ≥600 m² / g, a pore size of 5-12 nm, and a pore volume of 0.8-1.5 cm³ / g.

[0025] Step (2): Introduction of precursors using the dual-solvent method While continuously stirring, a mixed aqueous solution containing tantalum and scandium precursors is slowly added dropwise to the suspension obtained in step (1) to obtain an intermediate product in which the precursors are confined within mesoporous channels. The total volume of the mixed aqueous solution is determined based on the pore volume of the carrier to ensure that the aqueous phase is completely contained within the channels without overflowing into the external solvent phase. According to a specific embodiment, the volume of the mixed aqueous solution is 0.9-1.1 times the pore volume of the carrier. After adding the mixed aqueous solution, stirring can continue for 0.5-2 hours.

[0026] The core principle of this step lies in the immiscibility between the hydrophobic organic solvent and the hydrophilic aqueous solution, as well as the capillary effect of the mesoporous channels on the aqueous phase. Driven by thermodynamics, the aqueous solution containing metal ions is spontaneously and quantitatively drawn into the hydrophilic carrier channels. After the addition is complete, the external hydrophobic organic solvent phase is clear and transparent, directly indicating that the precursor has completely entered the channels. This mechanism eliminates the residue and aggregation of the precursor on the outer surface of the carrier from the outset, laying the foundation for subsequent high dispersion within the channels.

[0027] According to a specific embodiment, the tantalum precursor is a water-soluble tantalum-containing compound, and the scandium precursor is a water-soluble scandium-containing compound. The amounts of tantalum and scandium are determined based on the target loading, and the total loading of the active components is controlled to not exceed 1.0 wt%.

[0028] Step (3): Slow hydrolysis within a confined space The intermediate product obtained in step (2) was aged under sealed conditions in a constant temperature environment. The trace amount of water dissolved in the hydrophobic organic solvent was used to initiate the slow hydrolysis and in-situ nucleation of the precursor within the pores. The sealed conditions ensured that the hydrolysis rate was controlled by the limited trace amount of water within the system, avoiding the uncontrollable introduction of external water.

[0029] Within the confined space, each mesoporous channel functions as an independent nanoreactor. Due to the uniform distribution of precursor ions within the channels and the extremely low hydrolysis rate, the nucleation process proceeds slowly under kinetic control. The generated hydroxide species cannot acquire sufficient kinetic energy to migrate and aggregate across the pore walls, thus forming highly dispersed, isolated nucleation sites in situ on the inner surface of the channels. This step is crucial for achieving near-atomic dispersion.

[0030] Step (4): Washing and drying The solid material aged in step (3) is filtered and separated, then washed to remove residual solvent and unanchored ionic species, and then dried to obtain a tantalum-scandium hydroxide precursor confined within the pores. According to a specific embodiment, anhydrous ethanol can be used for washing, which can effectively remove residual n-hexane and unhydrolyzed precursor ions, while avoiding further hydrolysis and species migration that may be caused by water washing.

[0031] Step (5): Calcination and activation The precursor obtained in step (4) is placed in a programmed heating furnace and calcined at a low heating rate in an air atmosphere to the target temperature. It is then naturally cooled to room temperature to obtain the highly dispersed tantalum-scandium composite oxide catalyst.

[0032] Using a low heating rate avoids localized overheating and species thermal migration caused by excessively rapid heating, ensuring that the active components remain highly dispersed on the inner surface of the pores during the transformation of hydroxide to oxide. The presence of scandium oxide further isolates tantalum oxide species at the atomic scale, preventing thermal agglomeration during calcination.

[0033] According to the specific implementation method, the anhydrous hydrophobic organic solvent in step (1) is n-hexane; the tantalum precursor in step (2) is pentaethanol tantalum and the scandium precursor is scandium nitrate hexahydrate; the aging temperature in step (3) is 25-35℃ and the aging time is 24 hours; the heating rate in step (5) is 1℃ / min, the calcination temperature is 500-550℃ and the isothermal time is 4 hours.

[0034] According to the specific implementation method, after the mixed aqueous solution is added in step (2), the external hydrophobic organic solvent phase is clear and transparent.

[0035] The technical solution of the present invention will be described below through specific embodiments. It should be noted that these embodiments are only for the convenience of those skilled in the art and should not be regarded as a limitation on the scope of protection of the present invention. Unless otherwise specified, the reagents or materials used in the embodiments can be obtained commercially. The SBA-15 ordered mesoporous molecular sieve used in the following embodiments and comparative examples has a specific surface area of ​​720 m² / g, a pore size of 8.5 nm, and a pore volume of 1.15 cm³ / g.

[0036] Example 1 Example 1 describes the preparation of a 0.5 wt% Ta-0.12 wt% Sc / SBA-15 catalyst using the following method: (1) Pretreatment of the carrier: Take 1.0 g of SBA-15 carrier, vacuum dry it at 150 °C for 12 hours, transfer it to a nitrogen glove box, add 20 mL of anhydrous n-hexane, and magnetically stir to form a uniform suspension.

[0037] (2) Introduction of precursors using the dual-solvent method: Accurately weigh 0.015 g of tantalum pentaethanol and 0.009 g of scandium nitrate hexahydrate, and dissolve them together in 1.15 mL of deionized water to prepare a clear mixed precursor aqueous solution. Under vigorous stirring, add this aqueous solution dropwise to the suspension in step (1). After the addition is complete, the external n-hexane phase is clear and transparent, indicating that the aqueous phase has been completely absorbed into the pores. Continue stirring for 1 hour and let stand.

[0038] (3) Confined hydrolysis: The above mixture system was sealed and aged in a constant temperature water bath at 30 °C for 24 hours.

[0039] (4) Washing and drying: Filter, wash 3 times with anhydrous ethanol, and dry at 80 ℃ and normal pressure for 6 hours.

[0040] (5) Calcination: Under air atmosphere, the temperature is increased to 500 ℃ at 1 ℃ / min, and calcined at a constant temperature for 4 hours. After natural cooling, the target catalyst is obtained.

[0041] Analysis showed that the total loading of the active components of the catalyst was 0.62 wt%, and the molar ratio of scandium to tantalum was 0.5.

[0042] Example 2 Example 2 prepared a 0.3 wt%Ta-0.08 wt%Sc / SBA-15 catalyst. The preparation steps were the same as in Example 1, except that in step (2), the amount of tantalum pentaethanol was 0.009 g and the amount of scandium nitrate hexahydrate was 0.006 g.

[0043] The total loading of the active components of the obtained catalyst was 0.38 wt%, and the molar ratio of scandium to tantalum was 0.55.

[0044] Example 3 Example 3 prepared a 0.8 wt%Ta-0.20 wt%Sc / SBA-15 catalyst. The preparation steps were the same as in Example 1, except that in step (2), the amount of tantalum pentaethanol was 0.024 g and the amount of scandium nitrate hexahydrate was 0.015 g.

[0045] The total loading of the active components of the obtained catalyst was 1.0 wt%, and the molar ratio of scandium to tantalum was 0.5.

[0046] Example 4 Example 4 prepared a 0.5 wt%Ta-0.12 wt%Sc / SBA-15 catalyst. The preparation steps were the same as in Example 1, except that the aging temperature in step (3) was adjusted to 25 ℃ and the aging time was extended to 36 hours.

[0047] Example 5 Example 5 prepared a 0.5 wt%Ta-0.12 wt%Sc / SBA-15 catalyst. The preparation steps were the same as in Example 1, except that the calcination temperature in step (5) was adjusted to 550 ℃ and the heating rate was still 1 ℃ / min.

[0048] Comparative Example 1 Comparative Example 1 prepared 0.5 wt%Ta-0.12 wt%Sc / SBA-15 by an equal-volume impregnation method, comprising: Take 1.0 g of SBA-15 carrier, and add 1.15 mL of an aqueous solution containing 0.015 g of tantalum pentaethanol and 0.009 g of scandium nitrate hexahydrate to the carrier in one go. Stir well, let stand at room temperature for 12 hours, dry at 80 °C for 6 hours, and calcine at 500 °C for 4 hours. The metal types and loading are exactly the same as in Example 1.

[0049] Comparative Example 2 Comparative Example 2 prepared a single-component 0.5 wt% Ta / SBA-15 catalyst. The preparation steps were the same as in Example 1, except that the precursor solution in step (2) contained only 0.015 g of pentaethanol tantalum and no scandium precursor.

[0050] Comparative Example 3 Comparative Example 3 prepared a high-loading (3.0 wt% Ta-0.75 wt% Sc / SBA-15) using a dual-solvent method. The preparation steps were the same as in Example 1, except that in step (2), the amount of tantalum pentaethanol was increased to 0.090 g, and the amount of scandium nitrate hexahydrate was increased to 0.055 g. The total loading of the active components was 3.75 wt%.

[0051] The catalytic performance of the catalysts prepared in the above examples and comparative examples was evaluated according to the following method: A fixed-bed reactor was used, with a catalyst loading of 0.5 g, a reaction temperature of 350 °C, and atmospheric pressure. The feedstock was a mixture of ethanol and acetaldehyde in a molar ratio of 2.3:1. The feed mass hourly space velocity (WHSV) was 1.0 h⁻¹. - ¹. The product was analyzed online by gas chromatography. Samples were taken for analysis after the reaction had been running stably for 4 hours, and the results are shown in Table 1 below.

[0052] Table 1. Catalytic performance evaluation results

[0053] Note: The overall conversion rate is calculated based on the total number of moles of carbon in the feed, using the following formula: Total conversion rate = [(molar carbon of feed ethanol + molar carbon of feed acetaldehyde) - (molar carbon of discharge residual ethanol + molar carbon of discharge residual acetaldehyde)] / (molar carbon of feed ethanol + molar carbon of feed acetaldehyde) × 100%; Wherein, the number of carbon moles of each component = the amount of substance of the component (mol) × the number of carbon atoms in the molecular formula of the component.

[0054] The results above show that: (1) Comparison between Example 1 and Comparative Example 1: Under the same metal type and loading, the catalyst prepared by the method of the present invention has a total conversion rate that is nearly 30 percentage points higher, and a butadiene selectivity of up to 82.1%, which is nearly 34 percentage points higher than that of Comparative Example 1. The selectivity of ethylene and heavy by-products is extremely low, at 0.9% and 1.2%, respectively. Comparative Example 1, due to the use of the traditional impregnation method, resulted in severe agglomeration of the active components, with a total conversion rate of only 35.8% and a butadiene selectivity of less than 50%. A large amount of raw materials were consumed in side reactions such as ethylene and carbon deposition. This stark contrast directly demonstrates the decisive advantage of the dual-solvent-confined space in-situ growth method in achieving highly isolated dispersion of active components and suppressing strong acid cluster centers.

[0055] (2) Comparison of Example 1 and Comparative Example 2: Although the catalyst without Sc was prepared using the method of this invention, the total conversion rate decreased to 42.1%, the butadiene selectivity was only 55.3%, and the ethylene selectivity increased to 6.8%. This proves that scandium oxide has an atomic-scale effect on TaO. x Species play a crucial role in chemical isolation, not only helping to maintain the highly dispersed state of the active site, but also potentially enhancing the selectivity of the main reaction pathway by forming synergistic acid-base pairs with Ta sites.

[0056] (3) Comparison between Example 1 and Comparative Example 3: Even with the method of the present invention, when the total loading reaches 3.75 wt%, the total conversion rate drops to 41.5%, the butadiene selectivity is only 52.6%, and the ethylene selectivity increases to 10.3%. This shows that excessive loading will reduce the total conversion rate and butadiene selectivity.

[0057] (4) Catalyst stability: After 80 hours of continuous reaction, the total conversion rate of Example 1 remained above 60%, the butadiene selectivity remained above 78%, and the ethylene selectivity only slowly increased to 2.1%, demonstrating excellent long-term operational stability. In contrast, the butadiene selectivity of Comparative Example 1 dropped below 35% after 10 hours of operation, and the catalyst rapidly deactivated.

[0058] (5) Example 4 achieved the highest total conversion rate of 67.1% and excellent butadiene selectivity of 80.6% using a low-temperature slow hydrolysis method, indicating that lowering the hydrolysis temperature can further slow down the nucleation rate and is beneficial to a more uniform species distribution. Example 1 showed the best overall performance, with a butadiene selectivity of 82.1%, achieving the best balance between conversion rate and selectivity.

[0059] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention.

Claims

1. A highly dispersed tantalum-scandium composite oxide, characterized in that, It comprises a mesoporous silica carrier and an active component located on the inner surface of the mesoporous channels of the carrier; The active component is composed of tantalum oxide and scandium oxide, which are highly dispersed in the form of amorphous, sub-nanometer clusters or isolated atoms. Based on the total mass of the highly dispersed tantalum-scandium composite oxide, the total loading of tantalum and scandium elements in the active component does not exceed 1.0 wt%, and the molar ratio of scandium to tantalum is 0.2-0.

8.

2. The highly dispersed tantalum-scandium composite oxide according to claim 1, characterized in that, The loading of tantalum is 0.3-0.8 wt%, and the loading of scandium is 0.05-0.25 wt%.

3. The highly dispersed tantalum-scandium composite oxide according to claim 1, characterized in that, The mesoporous silica carrier is SBA-15, with a specific surface area ≥600 m² / g, a pore size of 5-12 nm, and a pore volume of 0.8-1.5 cm³ / g.

4. A method for preparing a highly dispersed tantalum-scandium composite oxide, characterized in that, The dual-solvent-confined space in-situ growth method includes the following steps: (1) The mesoporous silica support is vacuum dried, and then mixed with anhydrous hydrophobic organic solvent under an inert atmosphere and stirred to form a suspension; (2) While stirring, add dropwise a mixed aqueous solution containing tantalum precursor and scandium precursor to the suspension, wherein the volume of the mixed aqueous solution is 0.9-1.1 times the pore volume of the carrier, stir, and let stand; (3) The system obtained in step (2) is subjected to constant temperature static aging under sealed conditions to carry out slow hydrolysis in a confined space; (4) Filter, wash, and dry under normal pressure; (5) Under an air atmosphere, heat to a predetermined temperature, calcine at a constant temperature, and cool naturally to obtain the highly dispersed tantalum-scandium composite oxide.

5. The preparation method according to claim 4, characterized in that, The anhydrous hydrophobic organic solvent mentioned in step (1) is selected from one or more of n-hexane, cyclohexane, and n-heptane; and / or The tantalum precursor in step (2) is selected from one or two of pentaethanol tantalum and pentabutoxide tantalum, and the scandium precursor is selected from one or two of scandium nitrate and scandium chloride.

6. The preparation method according to claim 4, characterized in that, In the mixed aqueous solution described in step (2), the molar ratio of tantalum to scandium is 1:(0.2-0.8), and the total loading of tantalum and scandium does not exceed 1.0 wt%.

7. The preparation method according to claim 4, characterized in that, The vacuum drying temperature in step (1) is 120-180 degrees Celsius, and the vacuum drying time is 8-16 hours; and / or In step (3), the constant temperature aging temperature is 20-40 ℃, and the constant temperature aging time is 18-36 hours; and / or The atmospheric pressure drying temperature in step (4) is 60-100 ℃, and the atmospheric pressure drying time is 4-8 hours; and / or The predetermined temperature mentioned in step (5) is 450-600 ℃, and the temperature is increased to 450-600 ℃ at a heating rate of 0.5-2 ℃ / min, and then calcined at a constant temperature for 3-6 hours.

8. A highly dispersed tantalum-scandium composite oxide, characterized in that, Obtained by the preparation method according to any one of claims 4 to 7.

9. A method for preparing 1,3-butadiene from a catalytic mixture of ethanol and acetaldehyde, characterized in that, include: A catalytic reaction is carried out using a mixture of ethanol and acetaldehyde as raw materials, and adding the highly dispersed tantalum-scandium composite oxide as described in any one of claims 1-3 or the highly dispersed tantalum-scandium composite oxide as described in claim 8.

10. The method according to claim 9, characterized in that, The molar ratio of ethanol to acetaldehyde is (2.0-2.5):1; Optionally, the reaction temperature is 300-400 °C, the reaction pressure is atmospheric pressure, and the feed mass hourly space velocity is 0.5-2.0 h⁻¹. - ¹.

Citation Information

Patent Citations

  • Chromium-free catalyst as well as preparation method and application thereof

    CN114160144A